Ondansetron‐induced pseudoallergy with non‐ischemic myocardial injury: A rare case report of Kounis syndrome. Issue 12 (22nd December 2022) - Firew, Eden; Huang, Helen; Anand, Ayush; Asfaw, Yonathan Aliye; Parikh, Charmy; Khan, Hamza Rafique
Abstract: Ondansetron is an FDA‐approved selective serotonin 5‐HT3 receptor commonly indicated as an anti‐emetic agent for nausea and vomiting. It is rare to observe fatal reactions from ondansetron despite having no allergies or previous exposure. We report a case of anaphylactoid reaction with spontaneous coronary vasospasms in response to intravenous ondansetron. Abstract : Ondansetron is one of the most widely used antiemetic with a minimal side‐effect profile. It is rare to observe Kounis syndrome (KS) is multi‐factorial in pathology and should be approached with a high index of clinical suspicion.